LATIHAN UNTUK KESEHATAN JANTUNG TERHADAP TEKANAN DARAH PADA LANSIA DENGAN HIPERTENSI DI KELOMPOK LANSIA LATIHAN SEHAT DI RSUD DOLOPO - Nur Aini Fatimah; Achdyat Premedi; Wahyu Pujiati; Rahayu Budi Utama; Oktaffrastya W Septafani (PT Nuansa Fajar Cemerlang, 2026)
Intruduction: Hypertension is a cardiovascular problem that often occurs in the elderly. Hypertension is considered a serious health problem because its presence is often not realized and gets worse to the point of threatening the sufferer's life. One way to control hypertension in the elderly is through healthy heart exercise. Method: Pre-Experimental Design using a one group pretest post test design approach. The research was carried out on February 25 – March 19 2023 in the Healthy Heart Exercise Elderly Group at Dolopo Regional Hospital. The population of elderly people who actively participate in healthy heart exercise at Dolopo Regional Hospital is 35 elderly people, with a total sampling of 14 respondents. The independent variable is healthy heart exercise. The dependent variable is the level of hypertension in elderly people with hypertension. Processing Data with SPSS statistical tests using the Wilcoxon Signed Rank Test (α = 0.05). Results: From the research of 14 respondents, it was found that before doing healthy heart exercises, most of them had grade 1 hypertension blood pressure levels, 13 respondents (92.9%). After doing healthy heart exercises, 12 respondents (85.7%) obtained blood pressure levels in the high normal category. The results of statistical tests using the Wilcoxon Signed Rank Test showed that significance was 0.001. Because the ρ value ≤ 0.05, it can be concluded that there is a significant influence on blood pressure levels before and after the cardiac exercise intervention for the elderly. By regularly participating in Healthy Heart exercises, you can improve the health quality of life for the elderly by maintaining stable blood pressure in addition to taking hypertension medication regularly. Keywords: Healthy Heart Exercise, Blood Pressure, Elderly